Implementation of Sharia Insurance Risk Management - Hasibuan, Indra Mualim; Erianto, Ridho; Sugianto, Sugianto (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Every human activity can certainly have the potential for loss, and this potential is unpredictable. However, the level of loss can be minimized by registering with an insurance company. Insurance is a preparation made by a group of people, each of whom can experience unexpected losses. If the loss befalls one of those who are members of the group, then the loss will be borne jointly. This research is qualitative research using a library study analysis approach with documentation, data collection techniques, and written work of a bibliographic nature. This research aims to describe the implementation of Sharia insurance risk management. There are at least five ways that can be done in dealing with risk, firstly avoiding risk, secondly reducing risk by taking actions that can minimize losses, thirdly holding the risk yourself, fourthly sharing the risk with other parties, this concept is adopted by Sharia insurance as a basic concept and fifthly transfers risk by transferring the risk to another party, this risk transfer concept is then used as a basic concept in conventional-based insurance, where the potential risk to a person transferred to the insurance company.